Determination of Bisphenol a (BPA) migration in Şavak brine cheese stored in polyethylene terephthalate (PET) packaging by HPLC method - Tan, Sait; Demir, Pelin; Arslan, Ali (Wiley, 2024)
Bisphenol A (BPA) is a chemical compound widely used especially in the production of polycarbonate plastics and epoxy resins. BPA is a carcinogen and comes into foods due to plastic materials that come into contact with foodstuffs. The aim of this research was to determine the change in the BPA level in Savak brined white cheese during cold storage in polyethylene terephthalate (PET) packages. For this purpose, two groups were assigned as control (standard cheese produced by raw cow's milk) and BPA (cheese produced from the raw cow milk with 1 mg/L BPA added). The cheese samples were packed in PET packages containing, an 18% brine solution, and stored at +4(degrees)C for 270 days. The statistically significant difference was found in BPA levels between the control and BPA-added group in PET packages (P <= 0.05). The BPA levels in the brine solution and cheese of the control group were determined between 0.443-0.747 mu g/L and 0.927-1.237 mu g/kg, respectively. BPA levels in the brine and cheeses of the BPA-added group were between 1387-1894 mu g/L and 3702-4205 mu g/kg, respectively. The results showed that the using of BPA in cheese production leads to very high levels of BPA even during long storage and poses a risk to consumer health.
Keywords: Bisphenol A; Polyethylene terephthalate (PET); Migration; Savak brine cheese